EFFECTS OF AQUATIC ENVIRONMENTAL FACTORS ON BENTHIC MACROFAUNA: CASE STUDY OF PASAK RIVER IN THE URBAN AREA OF AYUTTHAYA PROVINCE - To-orn, Natthakitt (Srinakharinwirot University Journal of Sciences and Technology, 2021)
The purpose of this research was to study the composition and abundance of benthic macrofauna of Pasak River in urban area, Phra Nakhon Si Ayutthaya district, Phra Nakhon Si Ayutthaya province. Three transect lines from the sewage pipe of urban area were set up including (1) transect 1-upstream of the sewage pipe (2) transect 2-downstream of the sewage pipe, and (3) transect 3-opposite of the sewage pipe. Each transect contained five sampling points at distance of 5, 15, 25, 50 and 100 m. The macrofauna was classified into six major taxa including oligochaetes, polychaetes, gastropods, bivalves, crustaceans and insect larvae. The oligochaete families Tubificidae and Naididae, polychaete family Nephtyidae, and insect larvae family Chironomidae, which are the pollution tolerance species, mainly occurred in the area. Abundance of these benthic fauna was high in the sewage pipe and near sampling point. The distribution and abundances of macrofauna was closely related to total organic content and silt-clay fraction of sediment, water temperature, transparency and water pH. The study concluded that the dominant benthic macrofauna can be used as bioindicator to evaluate organic pollution in aquatic environment of urban area.